Linking microbial communities to rheumatoid arthritis: focus on gut, oral microbiome and their extracellular vesicles - Lu, Jian; Wang, Yi; Wu, Jing; Duan, Yusi; Zhang, Haifang; Du, Hong (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a severe, chronic autoimmune disease affecting approximately 1% of the global population. Research has demonstrated that microorganisms play a crucial role in the onset and progression of RA. This indicates that the disruption of immune homeostasis may originate from mucosal sites, such as the gut and oral cavity. In the intestines of patients in the preclinical stage of RA, an increased abundance of Prevotella species with a strong association to the disease was observed. In the oral cavity, infections by Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans can mediate the production of anti-citrullinated protein antibodies (ACPAs), potentially contributing to RA pathogenesis. Nevertheless, no single bacterial species has been consistently identified as the primary driver of RA. This review will discuss the connection between gut and oral bacteria in the development of arthritis. Additionally, it explores the role of bacterial extracellular vesicles (bEVs) in inducing inflammation and their potential pathogenic roles in RA.